2005
DOI: 10.1128/iai.73.4.2135-2146.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Type III Secretion Hierarchy of Translocators and Effectors in Attaching and Effacing Bacterial Pathogens

Abstract: Human enteropathogenic Escherichia coli (EPEC), enterohemorrhagic E. coli (EHEC), and the mouse pathogen Citrobacter rodentium (CR) belong to the family of attaching and effacing (A/E) bacterial pathogens. They possess the locus of enterocyte effacement (LEE) pathogenicity island, which encodes a type III secretion system. These pathogens secrete a number of proteins into culture media, including type III effector proteins and translocators that are required for the translocation of effectors into host cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
231
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(250 citation statements)
references
References 50 publications
17
231
1
1
Order By: Relevance
“…Recently, we demonstrated that the efficient secretion of many other EPEC type III effector proteins also required CesT (32,33), suggesting a possible interaction of these proteins with CesT. To identify new CesT interacting type III effector proteins, we took advantage of a ⌬sepD strain of EPEC that is known to hypersecrete type III effector proteins but not translocator proteins (38). ⌬sepD was cultured under conditions that promote type III effector secretion, and the culture supernatant was collected and passed over a CesT affinity column.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that the efficient secretion of many other EPEC type III effector proteins also required CesT (32,33), suggesting a possible interaction of these proteins with CesT. To identify new CesT interacting type III effector proteins, we took advantage of a ⌬sepD strain of EPEC that is known to hypersecrete type III effector proteins but not translocator proteins (38). ⌬sepD was cultured under conditions that promote type III effector secretion, and the culture supernatant was collected and passed over a CesT affinity column.…”
Section: Methodsmentioning
confidence: 99%
“…The primer pairs argH-F/ argH-R and lysA-F/lysA-R were used to screen by PCR for the ⌬argH and ⌬lysA mutants, respectively. The pRE-⌬lysA and pRE-⌬argH deletion constructs were sequentially introduced into an EPEC ⌬sepD⌬escN double mutant (25) to generate EPEC ⌬lysA-⌬argH⌬sepD⌬escN. Deletion constructs for EPEC escN (26) and sepD (25) in pRE112 were introduced into EPEC ⌬lysA⌬argH to generate EPEC ⌬lysA⌬argH⌬escN and ⌬lysA⌬argH⌬sepD, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The pRE-⌬lysA and pRE-⌬argH deletion constructs were sequentially introduced into an EPEC ⌬sepD⌬escN double mutant (25) to generate EPEC ⌬lysA-⌬argH⌬sepD⌬escN. Deletion constructs for EPEC escN (26) and sepD (25) in pRE112 were introduced into EPEC ⌬lysA⌬argH to generate EPEC ⌬lysA⌬argH⌬escN and ⌬lysA⌬argH⌬sepD, respectively. The four EPEC mutant strains, ⌬lysA⌬argH, ⌬lysA⌬argH⌬escN, ⌬lysA⌬argH⌬sepD, and ⌬lysA⌬argH⌬sepD⌬escN, were then used for SILAC analysis of their secreted proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Our understanding of EPEC and EHEC pathogenesis has benefited from the study of the mouse pathogen Citrobacter rodentium, which also expresses a T3SS encoded from a homologous locus of enterocyte effacement (LEE), and this pathogen forms characteristic attaching and effacing lesions in vivo and in eukaryotic HeLa cells Gruenheid et al, 2004;Mundy et al, 2004b). Through an understanding of the regulation of LEE expression in C. rodentium, a number of putative type III (T3)-secreted effector proteins have been identified (Deng et al, 2005). As the genes for these proteins are not encoded on the LEE, they are termed non-LEE-encoded effector (Nle) proteins.…”
Section: Introductionmentioning
confidence: 99%